Late Pleistocene Caprinae assemblages of Tham Lod Rockshelter (Mae Hong Son Province, Northwest Thailand). (10th November 2018) - Wattanapituksakul, Athiwat; Filoux, Arnaud; Amphansri, Anusorn; Tumpeesuwan, Sakboworn
Abstract: The Late Pleistocene archeological site of Tham Lod Rockshelter has yielded a large number of animal remains associated with a rich lithic assemblage with a Hoabinian facies. The well-preserved collection of Caprinae dental material was analyzed and attributed to three Caprinae species. The morphological and metrical analysis allowed the identification of the Sumatran serow ( Capricornis sumatraensis), the Chinese goral ( Naemorhedus griseus ), and the Himalayan goral ( N. goral ). To understand the relation between the Caprinae and the prehistoric hunter-gatherers, the paleodemography of the three species was reconstructed using age estimation at the death based on tooth wear. The mortality profile revealed that the Homo sapiens hunter-gatherers adopt a generalized subsistence strategy for these preys. This new data contribute to our knowledge on the mammalian biodiversity during the Late Pleistocene in Southeast Asia and add new information about the subsistence behavior of prehistoric hunter-gatherers in northern Thailand.